'Just because you are dead, doesn't mean you haven't got opinions': a conversation with Doreen Massey. Issue 4 (4th July 2022) - Marriott, James
ABSTRACT: A conversation with Doreen Massey after her passing. A meditation on memory, on how the living can keep in dialogue with the dead and continue to be guided by their thought, and the role of the book as a carrier of ideas. On Massey's exploration of the theoretical frame of 'settlements', it's application to the political turbulence of 2015–2017, and how the nature and character of people are being altered by these times.